Micro and Nano Structural Analysis of Dental Ceramic and Luting Resin Interface and the Effect of Water Exposure on Integrity of Cement Interface - Ramakrishnaiah R; Alaqeel SM; Alkheraif AA; Divakar DD; Elsharawy M; Matinlinna JP; Vallittu PK (AMER SCIENTIFIC PUBLISHERS, 2025)
The current study was aimed to evaluate-by micro and nano-structural analysis-the interface between dental ceramic and resin materials. The degree of resin impregnation into the etched micro patterns, the nano-mechanical properties of the resin-ceramic interface and the effect of subjecting to exposure in boiling water on resin-ceramic interface were studied. Three silica based glass ceramics were compared and contrasted: twenty samples from Computer Aided Design (CAD) blocks of each material were prepared. The specimens were finished, polished, ultrasonically cleaned, and etched with suitable acid. The specimens were randomly divided into two study groups to evaluate the effect of primer on resin cement impregnation. Each group of specimens were further divided into two subgroups to compare and contrast the difference in resin impregnation between adhesive resin and resin composite cement. The resin-ceramic interface was examined under scanning electron microscope and nano-mechanical properties were analyzed using a nano-indenter. The results were statistically analyzed using multivariate analysis of variance, a post hoc test, and regression analysis at a significance level of p<0.05. The results showed better resin impregnation of adhesive resin on primer treated specimens than resin composite cement. The specimens with the primer treatment and application of adhesive resin exhibited higher elastic moduli (46.07 GPa) and nano-hardness (2.02 GPa) even after subjecting to exposure in boiling water.